INTERNATIONAL POLICY BETWEEN UKRAINE AND GERMANY: CHARACTERISTIC FEATURES OF THE DEVELOPMENT OF THEIR RELATIONS - Siekunova, Yuliia; Veber, Veronika (Sworld-Us Conference proceedings, 2022)
The work investigates the characteristic features of the development of political relations between Ukraine and Germany at the current stage.